Continuities and change in alcohol policy at the global level: a documentary analysis of the 2010 Global Strategy for Reducing the Harmful Use of Alcohol and the Global Alcohol Action Plan 2022-2030 - Matthew Lesch; Jim McCambridge (BMC, 2024)
Abstract Background There are only two major statements which define alcohol policy development at the global level. There has not been any comparative analysis of the details of these key texts, published in 2010 and 2022 respectively, including how far they constitute similar or evolving approaches to alcohol harm. Methods Preparatory data collection involved examination of documents associated with the final policy statements. A thematic analysis across the two policy documents was performed to generate understanding of continuity and change based on comparative study. Study findings are interpreted in the contexts of the evolving conceptual and empirical literatures. Results Both documents exhibit shared guiding principles and identify similar governance challenges, albeit with varying priority levels. There is more emphasis on the high-impact interventions on price, availability and marketing in 2022, and more stringent targets have been set for 2030 in declaring alcohol as a public health priority therein, reflecting the action-oriented nature of the Plan. The identified roles of policy actors have largely remained unchanged, albeit with greater specificity in the more recent statement, appropriately so because it is concerned with implementation. The major exception, and the key difference in the documents, regards the alcohol industry, which is perceived primarily as a threat to public health in 2022 due to commercial activities harmful to health and because policy interference has slowed progress. Conclusions The adoption of the Global Alcohol Action Plan 2022-30 potentially marks a pivotal moment in global alcohol policy development, though it is unclear how fully it may be implemented. Perhaps, the key advances lie in advancing the ambitions of alcohol policy and clearly identifying that the alcohol industry should not be seen as any kind of partner in public health policymaking, which will permit progress to the extent that this influences what actually happens in alcohol policy at the national level.